Total knee arthroplasty in patients with rheumatoid arthritis – midterm results - Blagojević, Zoran; Gluščević, Boris; Djordjević, Boban (Vojnosanitetski pregled, 2017)
Background/Aim. Total knee arthroplasty in patients with rheumatoid arthritis is an effective method of eliminating pain and improving functional status, but it is associated with a number of unique challenges. The aim of this study was to evaluate the clinical and radiographic outcomes of total knee arthroplasty, as well as patient satisfaction, in this series of patients with rheumatoid arthritis. Methods. Between January 2001 and 2012, 108 total knee arthroplasties in 78 patients with rheumatoid arthritis were performed, utilizing a posterior-stabilized prostheses. The average age of the patients was 58 ± 12.4 years, and 88% were females. Median follow-up of patients was 80 months with interquartile range of 34 months (min-max: 36-132 months). Results. Average Knee Society score improved from preoperative 18 ± 11.4 to postoperative 83 ± 3.5, and Functional Knee Society score from 21 ± 9.9 to 50 ± 5.9. Western Ontario and McMaster Universities Arthritis (WOMAC) knee injury and osteopaedic outcome scores improved from 23 ± 6.4 to 69 ± 4.6 postoperatively. In 25 (23.14%) knees radiolucent lines of less than 2 mm were found and they were not progressive. Survival rate excluding deep infection was 99.1%. Conclusion. Total knee arthroplasty is an effective procedure of treatment of damaged knee joint in patients with rheumatoid arthritis.